IMPROVING STUDENTS’ PRONUNCIATION BY USING MINIMAL PAIRS DRILL IN JUNIOR HIGH SCHOOL - Isnani, .; Supardi, Iwan; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract: This research was conducted using Classroom Action Research to improve students? English pronunciation by using minimal pairs drill technique. The subject of this research was the eight grade students in class F of SMP Negeri 2 Pontianak which consisted of 35 students. This research was done in two cycles. The first cycle was done on April 30th 2016 and the second cycle was done on May 3rd 2016 in which the meeting end for forty-five minutes. To obtain the data, the writer administered oral test to pronounced some words in every cycle. The writer also used observation checklist table and field notes were applied to reflect the students? improvement in their pronunciation in every cycle. In the first cycle, the students? mean score was 62.42 which categorized as ?good? but it was not satisfying. Then, in the second cycle, the students? mean score was 81.86 which categorized as ?excellent? and it was satisfying. Based on the students? mean score, it was found that the students? pronunciation improved from the first cycle to the second cycle. Keywords: Improvement, Pronunciation, Minimal Pairs Drill Abstrak: Penelitian ini dilakukan dengan menggunakan Penelitian Tindakan Kelas untuk meningkatkan kemampuan pengucapan bahasa Inggris siswa dengan menggunakan teknik latihan pasangan minimal. Subjek penelitian ini adalah siswa kelas VIII F SMP Negeri 2 Pontianak yang terdiri dari 35 siswa. Penelitian ini dilakukan dalam dua siklus. Siklus yang pertama dilaksanakan pada tanggal 30 April 2016 dan siklus yang kedua dilaksanakan pada tanggal 3 Mei 2016 yang mana pertemuan diakhiri sekitar 45 menit. Untuk mendapatkan data, penulis memberikan tes lisan dalam setiap siklus. Penulis juga menggunakan daftar tabel observasi dan catatan yang diterapkan untuk mencerminkan peningkatan siswa dalam pengucapan mereka pada setiap siklus. Pada siklus yang pertama, skor rata-rata yaitu 62.42 dengan kategori ?baik? tetapi tidak memuaskan. Kemudian, pada siklus yang kedua, skor rata-rata yaitu 81.86 dengan kategori 'sangat baik' dan memuaskan. Berdasarkan skor rata-rata tersebut bahwa kemampuan pengucapan siswa meningkat dari siklus pertama ke siklus kedua. Kata Kunci: Peningkatan, Pengucapan, Latihan Bunyi Berpasangan